Autonomy support and motivation in private music students: the role of basic psychological needs - Xiong, Qin; Mohamad Haris, Mohamad Fitri (Institute of Advanced Engineering and Science, 2025)
The objective of this research was to measure the impact of autonomous support and expectancy beliefs on autonomous motivation of students. The study investigated the impact of basic psychological needs on autonomous support. Furthermore, the mediating role of basic psychological needs is also analyzed. Using simple random sampling, the study collected cross-sectional data from 305 students on a Likert scale questionnaire at private music schools located in Nanchang, China. SPSS 26 and Smart PLS 4 are used for descriptive and inferential statistics and findings. The study found that autonomy support, expectancy beliefs and basic psychological needs have a significant impact on autonomous motivation. The study also found that autonomy support and expectancy beliefs also have significant influence on basic psychological needs. While the study found that basic psychological needs mediate the impact of autonomy support and expected beliefs on autonomous motivation. In addition, measuring the dimension of autonomous support, the study found that parental support and teachers’ support have a significant impact on autonomous motivation. While the study found that parental support and teachers’ support also have a significant impact on basic psychological needs. The study further confirmed that basic psychological needs positively mediate the impact of parental support and teachers’ support on autonomous motivation.